Glucocorticoid‐mediated repression of T‐cell receptor signalling is impaired in glucocorticoid receptor exon 2‐disrupted mice. Issue 2 (12th November 2013) - Liddicoat, Douglas R; Purton, Jared F; Cole, Timothy J; Godfrey, Dale I
Abstract : Studies using glucocorticoid receptor exon 2‐disrupted knockout (GR2KO) mice provided strong evidence against an obligatory role for glucocorticoid receptor (GR) signalling in T‐cell selection. These mice express a truncated form of the GR that is incapable of transmitting a range of glucocorticoid (GC)‐induced signals, including GC‐induced thymocyte death. However, one study that suggested that truncated GR function is preserved in the context of GR‐mediated repression of T‐cell activation‐induced genes, challenged earlier conclusions derived from the use of these mice. Because GR versus T‐cell receptor (TCR) signalling cross‐talk is the means by which GCs are hypothesized to have a role in T‐cell selection, we reassessed the utility of GR2KO mice to study the role of the GR in this process. Here, we show that GR‐mediated repression of TCR signalling is impaired in GR2KO T cells in terms of TCR‐induced activation, proliferation and cytokine production. GC‐induced apoptosis was largely abolished in peripheral T cells, and induction of the GC‐responsive molecule, interleukin‐7 receptor, was also severely reduced in GR2KO thymocytes. Together, these data strongly re‐affirm conclusions derived from earlier studies of these mice that the GR is not obligatory for normal T‐cell selection.